PENGGUNAAN MEDIA TANAMAN LOKAL UNTUK MENINGKATKAN AKTIVITAS BELAJAR IPA DI SEKOLAH DASAR - Maria Dolorosa Roru; Nining Sar'iyyah; Stefanus Tebajak Henakin (Prima Magistra: Jurnal Ilmiah Kependidikan, 2020)
The purpose of this study is (1) To find out the Application of Local Plant Media in Increasing Student Learning Activities of Grade IV SDI Onekore 4, Ende Utara District, Ende Regency. (2). To find out the increase in student learning activities in class IV SDI Onekore 4, Ende Utara District, Ende Regency. This type of research used is classroom action research. The subjects in this study were 32 students in grade IV Onekore 4 SDI. Furthermore, data collection techniques are carried out through observation and tests. Based on the results of this study it can be concluded that the use of local plant media to identify science learning activities in class IV SDI Onekore 4 from cycle I to cycle II has increased. Cycle I obtained an average yield of 59.84 and in the cycle obtained an average of 70.80. From the results of the study it can be concluded that the science learning process by using local plant media can increase the learning activities of grade IV students of SDI Onekore 4, Ende Utara subdistrict, Ende Regency.